El control de mérito en la acción extraordinaria de protección como facultad garantista ejercida por la Corte Constitucional - Cisneros Rodríguez, Josuha Cisneros (2023)
ABSTRACT: The main objective of this research study was to focus on the control of merit in the extraordinary action of protection is the power of the Constitutional Court to review the facts of the underlying guarantee, in addition to the existence of a violation of rights in the exercise of jurisdictional authority. This research project aims to determine whether this power is compatible with the theoretical model of "guarantees" and, consequently, with the Ecuadorian constitutional system. For this purpose, documentary-bibliographic and descriptive research is carried out, resorting mainly to the analysis of constitutional doctrine and jurisprudence on the control of merit, its requirements and criticisms, and the model of guarantors. Following this analysis, a critique is made of the Constitutional Court's discretion in exercising this power. It concludes that the control of merit is a guaranteeing power as long as this inevitable jurisdictional discretion is reduced to the minimum possible, for which a change in jurisprudence is proposed.